Long-term prognosis and quality of life in patients with early rheumatoid arthritis treated according to the 2015 ACR guideline (LELAND): protocol for a multicentre prospective observational study in Southern China. Issue 11 (15th November 2018) - Zhao, Jinjun; Zhan, Taihe; Zhu, Junqing; Fan, Meida; Huang, Qin; Ren, Hao; Wu, Jing; Yu, Qinghong; Lin, Jingli; Ouyang, Qingqing; An, Shengli; Yang, Min
Abstract : Introduction: Rheumatoid arthritis (RA) is a chronic systemic disease and one of the most disabling diseases for patients. The American College of Rheumatology (ACR) issued a new guideline in 2015 for the treatment of RA based on the treat-to-target strategy to achieve better outcomes. This study will focus on the real-world rates of remission and low disease activity of patients with early RA in China, who will be treated according to the 2015 ACR guideline. Additionally, factors influencing treat-to-target outcomes will be analysed, and long-term prognosis and quality of life will be assessed. Method and analysis: Two-hundred patients with early RA will be enrolled, treated and followed up once every 3 months for 48 months. These patients should fulfil the 2010 RA classification criteria of the ACR/European League Against Rheumatism with a disease course of no more than 6 months and should also fulfil other eligibility criteria. The patients will be treated following the 2015 ACR guideline. Their disease activity will be assessed, and they will be instructed to complete several questionnaires once every 3 months. The primary outcomes are the Disease Activity Score on 28 joints and Health Assessment Questionnaire Disability Index. The secondary outcome variables are the Simplified Disease Activity Index, Clinical Disease Activity Index and Routine Assessment of Patient Index Data 3 results, imaging data and personal medical costs. The data will be analysed using appropriate statistical analyses. Ethics and dissemination: This research was approved by the Nanfang Hospital Ethics Committee (NFEC-2017–192). The results of the study will be published in international peer-reviewed journals. Trial registration number: NCT03508713 ; Pre-results.